2016
DOI: 10.1186/s13741-015-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training (HIT) for effective and time-efficient pre-surgical exercise interventions

Abstract: The advancement of perioperative medicine is leading to greater diversity in development of pre-surgical interventions, implemented to reduce patient surgical risk and enhance post-surgical recovery. Of these interventions, the prescription of pre-operative exercise training is gathering momentum as a realistic means for enhancing patient surgical outcome. Indeed, the general benefits of exercise training have the potential to pre-operatively optimise several pre-surgical risks factors, including cardiorespira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 92 publications
(145 reference statements)
1
52
0
4
Order By: Relevance
“…While high-intensity interval training has promise for the effective and time-efficient enhancement of pre-surgery fitness (Weston et al, 2016), it is not yet known whether patients with large abdominal aortic aneurysms can exercise at a high intensity while remaining within safe blood pressure and heart rate limits. Using the HIT-AAA trial data, our aim here was to undertake a detailed evaluation of the exercise sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While high-intensity interval training has promise for the effective and time-efficient enhancement of pre-surgery fitness (Weston et al, 2016), it is not yet known whether patients with large abdominal aortic aneurysms can exercise at a high intensity while remaining within safe blood pressure and heart rate limits. Using the HIT-AAA trial data, our aim here was to undertake a detailed evaluation of the exercise sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prolonged periods of physical inactivity in the post-operative phase induce a loss of muscle mass, cardiopulmonary deconditioning, pulmonary complications, and psychological distress (Pouwels et al, 2016), all of which can be offset by enhanced fitness. Pre-surgical exercise training therefore represents an encouraging means of improving surgical outcome (Weston et al, 2016) and is potentially beneficial for patients with abdominal aortic aneurysm disease (Pouwels et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid a reduced sample size by using standard repeated measure techniques, we chose to analyze the time course of the aerobic capacity and the muscle function measurements with a mixed models analysis. This multilevel approach has been proven to be a useful method to study changes over time in studies with missing data and this method gives unbiased estimates, makes it possible to include covariates and takes into account the dependency between different measurements within a patient [48]. Our data were collected between the years 2006 and 2008 and therefore, current management of oncological surgery patients might have changed.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] In a similar comparative meta-analysis of 277 patients with CHD, Elliot and colleagues demonstrated that HIIT was associated with a significantly higher VO2, which is independently associated with reduced CVD mortality. 51 Larger national cohort studies across the globe support these findings in disease- 53,54 In case control and cohort studies of CHD patients, high intensity ET has been shown to elicit higher aerobic capacity, improved endothelial function, and enhanced HRQoL.…”
Section: Role Of Exercise Intensitymentioning
confidence: 99%